Digital co-production as an approach to citizens’ participation in disaster risk reduction and management: A qualitative case on local government units - Pitogo, Vicente A (Animo Repository, 2021)
In the twenty-first century, disaster management (DM) has been at the forefront of research as governments worldwide have faced enormous issues related to an overwhelming and impending size of disaster occurrences. (DM) has been constructed and emerged as a method and a strategy in reducing the impact of the disaster on persons and structures that can potentially cause social and economic disruptions to boost disaster preparedness and recovery. Parallel to this, professionals in the area and existing literature are constantly debating the significance and role of information and communications technology (ICT) in disaster management in overcoming the posed issues. As a result, ICT must be developed to promote innovation and collaboration between the government and the general public. The growing and dynamic character of people's willingness to participate and co-produce in technology-enabled disaster management, on the other hand, has to be investigated further. This dissertation looks at how digital co-production was implemented in an ICT-based disaster management platform in Naga city in Bicol Region and Caraga Region's select local government units. Factors that influence citizens to participate in co-producing disaster-related information, such as awareness and perspicacity, scientific know-how, altruism, and public governance support, have been discovered using a qualitative technique called reflexive thematic analysis. It was also found that citizen engagement in an ICT-based disaster management framework is facilitated by technology championing, digital volunteerism, and community collaboration. In the context of the digital divide, political dynamics, and interagency cooperation, additional challenges emerged in the research. Most ICT-based platforms were used in the pre-disaster and disaster phases. Only social media was used post-disaster to provide reports and information relevant to specific disasters that affected the community. In the deployment of technology-based disaster management among LGUs, digital co-production has substantially improved. It was also discovered that digital co-production does not thrive in a particular LGU because LGUs have different management styles, priorities, and prerogatives. In the context of disaster management, it has also brought depth to the theory. However, a few areas that need to be examined for future research involvement that could enhance new learnings and insights in co-production processes have been identified. Keywords: disaster management, digital co-production, qualitative case study, reflexive thematic analysis.